2002
DOI: 10.1038/nn792
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin regulates G protein–stimulated adenylyl cyclase activity

Abstract: Neurofibromatosis type 1 (NF1) is a dominant genetic disorder characterized by multiple benign and malignant nervous system tumors, and by learning defects in 45% of children with NF1 mutations. Studies of neurofibromin, the protein encoded by NF1, have focused on its functions in tumorigenesis and regulation of Ras activity; however, Drosophila NF1 regulates both Ras and cyclic AMP (cAMP) pathways. Expression of a human NF1 transgene rescued cAMP-related phenotypes in NF1 mutant flies (small body size and G p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
181
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(189 citation statements)
references
References 14 publications
5
181
2
1
Order By: Relevance
“…Previous studies from our laboratory and others have shown that neurofibromin positively regulates cyclic adenosine monophosphate (cAMP) levels (Tong et al, 2002;Dasgupta et al, 2003) in the brain in addition to negatively regulating Ras activity. The regulation of both Ras and cAMP is one of the properties of G-protein-coupled receptors, which suggests that chemokines present in the tumor microenvironment might increase Nf1 À/À astrocyte growth.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%
“…Previous studies from our laboratory and others have shown that neurofibromin positively regulates cyclic adenosine monophosphate (cAMP) levels (Tong et al, 2002;Dasgupta et al, 2003) in the brain in addition to negatively regulating Ras activity. The regulation of both Ras and cAMP is one of the properties of G-protein-coupled receptors, which suggests that chemokines present in the tumor microenvironment might increase Nf1 À/À astrocyte growth.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%
“…A functional GAP domain encoded within neurofibromin attenuates Ras function by rapidly converting active GTP-Ras to the inactive GDP form (Adjei, 2001). As a result, a number of laboratories have undertaken studies to address the specific involvement of neurofibromin in the posttranslational regulation of Ras and downstream MAP kinase and adenylyl cyclase pathways (Kim et al, 2001;Tong et al, 2002). In contrast, a basic understanding of the transcriptional regulation of the NF1 gene is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Neurofibromin down-regulates RAS signaling by accelerating the conversion of active RAS-guanosine triphosphate (GTP) to inactive RAS-guanosine diphosphate (GDP) (8,9). The resulting decreased expression of neurofibromin leads to activation of several important downstream signaling pathways, including mitogen extracellular signal-regulated Kinase (MEK)/mitogen activated protein kinase (MAPK) and cyclic adenosine monophosphate (cAMP)-mediated protein kinase A (PKA) pathways (10,11). Just how these defects in multiple signaling pathways cause the specific alterations of pigmentation originally observed in patients is not yet clear.…”
mentioning
confidence: 99%